PENERAPAN MODEL PEMBELAJARAN BERBASIS RISET UNTUK MENINGKATKAN PENGUASAAN MATERI FLUIDA DINAMIS - Lukas M Wacanno; Elsina S Tamaela; Asry N Latupeirissa (Science Map Journal, 2023)
The research aims to determine the improvement of mastery of dynamic fluid material by using a research-based learning model for students, class XI IPA-2 SMA Kristen 1 Amahai. This type of research is a descriptive study with a one-group pretest-postest research design, in 19 students as a research sample obtained using the Purposive Sampling technique. The data of this study were collected using test and non-test instruments (LKPD) and then analyzed descriptively. The results showed that in the initial test 100% of students were in a failed qualification with an average score of 11.00. The results of the analysis of cognitive abilities of students during the learning process showed that the average score of students was 88.4 with good qualifications and the average score of the final test achievement of students was 81.5 which was in good qualifications. The average result of the N-gain test of learners was 0.79 at high qualifications. Thus, it can be concluded that there is an increase in mastery of the material after students are taught using a research-based learning model